Vestibulo-Ocular Reflex Function and Its Impact on Postural Stability and Quality of Life in Cochlear Implant Recipients: A Cross-Sectional Study - Khalid A. Alahmari; Sarah Alshehri (Life)
Background/Objectives: Vestibulo-ocular reflex (VOR) function, measured by the video head impulse test (vHIT) gains, plays a crucial role in postural stability and quality of life. Cochlear implant recipients often experience vestibular dysfunction, but its relationship with balance and patient-reported outcomes remains underexplored. This study aimed to (1) evaluate the relationship between vHIT gains and postural stability in cochlear implant recipients; (2) assess the impact of vHIT gains on quality-of-life metrics; and (3) identify key predictors of postural stability, including vHIT gains and demographic/clinical characteristics. Methods: This cross-sectional study was conducted between August 2023 and February 2024 and included 46 participants that comprised cochlear implant recipients and age-matched normal hearers who underwent the vHIT for lateral, anterior, and posterior semicircular canal function. Postural stability was assessed using dynamic posturography, and quality of life was measured using the Short Form-36 (SF-36). Multiple linear regression and correlation analyses were performed. Results: The vHIT gains demonstrated significant positive correlations with postural stability, with the lateral canal showing the strongest association (r = 0.742, p = 0.001), followed by the posterior (r = 0.701, p = 0.003) and anterior canals (r = 0.684, p = 0.005). A multiple regression analysis identified the lateral canal as the most significant predictor of postural stability (β = 0.512, p = 0.001, adjusted R2 = 0.47). Quality-of-life metrics were inversely correlated with the vHIT gains, particularly in the posterior canal (r = −0.712, p = 0.002), which explained 43–51% of the variance. Conclusions: This study highlighted the lateral semicircular canal as the primary determinant of postural stability in cochlear implant recipients, underscoring the importance of vestibular assessments in optimizing balance and functional outcomes.